2010
DOI: 10.1042/bj20091745
|View full text |Cite
|
Sign up to set email alerts
|

The Ig-like domain of human GM-CSF receptor α plays a critical role in cytokine binding and receptor activation

Abstract: GM-CSF (granulocyte/macrophage colony-stimulating factor) is an important mediator of inducible haemopoiesis and inflammation, and has a critical role in the function of alveolar macrophages. Its clinical applications include the mobilization of haemopoietic progenitors, and a role as an immune stimulant and vaccine adjuvant in cancer patients. GM-CSF signals via a specific alpha receptor (GM-CSFRalpha) and the shared hbetac (human common beta-subunit). The present study has investigated the role of the Ig-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 47 publications
5
19
0
Order By: Relevance
“…By identifying a naturally occurring splice variant of the IL-3 ␣-subunit termed SP2 that lacks the N-terminal Ig-like domain that is otherwise present in the full-length receptor (termed SP1) in addition to the membrane-proximal cytokine receptor homology module (16), we have uncovered additional complexity within the IL-3 receptor system that would enable IL-3 to activate distinct signaling outcomes. Interestingly, whereas the IL-3R␣ subunits in both mouse and humans exist as either SP1 or SP2 splice variants, no such naturally occurring isoforms have been identified in the related GM-CSF or IL-5 ␣ receptors (38), consistent with the essential roles of the N-terminal Ig-like domains within these ␣-subunits for receptor activation (38,40).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…By identifying a naturally occurring splice variant of the IL-3 ␣-subunit termed SP2 that lacks the N-terminal Ig-like domain that is otherwise present in the full-length receptor (termed SP1) in addition to the membrane-proximal cytokine receptor homology module (16), we have uncovered additional complexity within the IL-3 receptor system that would enable IL-3 to activate distinct signaling outcomes. Interestingly, whereas the IL-3R␣ subunits in both mouse and humans exist as either SP1 or SP2 splice variants, no such naturally occurring isoforms have been identified in the related GM-CSF or IL-5 ␣ receptors (38), consistent with the essential roles of the N-terminal Ig-like domains within these ␣-subunits for receptor activation (38,40).…”
Section: Discussionmentioning
confidence: 96%
“…Overall, we conclude that despite being properly transported to the cell surface, the hIL-3R␣ SP2 subunit exhibits a lower propensity to engage in high affinity hIL-3 binding in CTLL2 cells. This situation clearly differs from the Ig-like domain deletion mutants of the mouse and human IL-6␣ receptor, which fail to localize to the cell surface (37), and the human GM-CSF recep- tor ␣-subunit, which requires its Ig-like domain for high affinity GM-CSF binding and normal receptor activation (38).…”
Section: Hil-3⅐h␤c Binding Interfaces In Complexes With Hil-3r␣ Sp1mentioning
confidence: 92%
“…Additionally, homology modeling and mutagenesis have indicated that the surface of human GM-CSF that mediates R-receptor binding will be larger than that revealed by the complex crystal structure, as no electron density was observed for the GM-CSFRR N-terminal Ig-like domain: a domain since shown to play an important role in GM-CSF binding. 49 ' DISCUSSION Although mIL-3 conveys essential biological signals in blood cell development and inflammatory responses, structural studies of this important protein have been confounded by its intrinsic poor solubility and strong tendency to aggregate in solution. A recently developed soluble variant of mIL-3, mIL-3 , which retains wild-type biological activity and exhibits significantly improved solution behavior, 11 has enabled us to perform a comprehensive characterization of its 3D solution structure, backbone dynamics, and hydrodynamic properties in two different buffer solutions over the temperature range 283-303 K. We begin by comparing the structure of mIL-3 with structures of the hIL-3 analogue SC-55494, GM-CSF, and IL-5 and then evaluate the novel features of mIL-3 33-156 revealed in the current study.…”
Section: Backbone 15 N-relaxation Dispersion Measurementsmentioning
confidence: 99%
“…Purified hIL-3 (13-125; W13Y) was radio-iodinated using Pierce Pre-Coated Iodination tubes (Thermo Scientific) according to established protocols [22,23]. COS cells were transfected by electroporation with expression plasmids encoding the human IL-3Rα subunit (pSG5: IL‑3Rα) and the human βc subunit (pSG5: βc).…”
Section: Methodsmentioning
confidence: 99%